Blind separation of speech mixtures - Vaninirappuputhenpurayil Gopalan Reju (2010)
This thesis addresses three well-known problems in blind source separation of speech signals, namely permutation problem in the frequency domain blind source separation (BSS), underdetermined instantaneous BSS and underdetermined convolutive BSS.